Unveiling challenges and opportunities in the integration of emerging technologies in the accounting profession: a preliminary investigation - Adriana Shamsudin; Mohd Noor Azli Ali Khan; Ahmad Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2025)
Business processes are undergoing significant evolution with the advent of cutting-edge technologies such as Artificial Intelligence, Big Data, Robotic Process Automation, Cloud Computing, Blockchain, Internet of Things, and XBRL. Despite these advancements, the accounting profession has faced criticism for appearing to lag behind other industries in technological integration. This study aims to investigate the challenges associated with the integration of emerging technologies in the accounting profession, despite the numerous potential opportunities they offer. To map the opportunities and challenges of emerging technologies in the accounting profession, the Technology-Organisation-Environment (TOE) framework has been employed. This research employs a qualitative methodology, through semi-structured interviews with eleven (11) practitioners from diverse accounting backgrounds representing their organisations. These interviews provide initial insights into the adoption of emerging technologies in current accounting practices, particularly in Malaysia. The analysis comprehensively discusses opportunities and challenges of technology adoption through nine (9) aspects of organisation including technological availability, relative advantage, compatibility, top management support, technology competence, cost, organisational change adaptability, government support and regulation, and environmental uncertainty. This paper contributes to the accounting profession by offering insights into strategies that firms, vendors, and government entities can adopt to successfully implement emerging technologies.